Darwinism in a medical school - Sthapit, B; Dhungana, V (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v7i2.2718 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 183-184